Compromisso social do psicólogo em artigos publicados em periódicos científicos no Brasil - Amorim, Keyla Mafalda de Oliveira (2010)
Psychologist s social commitment in scientific articles published in scientific papers in Brazil. A situation analysis of the scientific production concerning psychologist s social commitment can aid the historical constitution of this theme and also subsidize reflections about the course of this profession in Brazil. In order to contribute to this debate, the theme social commitment of psychologist was analyzed in the scientific literature concerning psychologist profession in the country. Specifically, papers about the profession that mentioned the theme social commitment were characterized and their approach of this matter was analyzed. In order to accomplish these goals, two research stages were fulfilled: first, in a systematic search for scientific literature in internet databases, studies about the psychologist profession in the country were gathered; in the second stage, scientific papers relating to social commitment in their titles, abstracts or keywords were selected. 61 papers were retrieved, organized in electronic database and full-text analyzed, based in two axis: scientometric and thematic. The papers were identified, in general, as recent, of theoretic character and aligned with several Psychology subareas; mainly produced in public universities, in country s southwest; were of conjunctural interest to the authors research projects, individually published, by professors in touch with post-graduation; published in open access journals, with high Qualis evaluation. It was verified that there is no consensus on the meaning of the theme, prevailing definitions concerning the understanding of the social reality, to the majority of people or to a progressive-aligned professional performance. Are adduced as committed agents: the psychologist (sometimes together with other kinds of professionals or with users), the academia, and the representative entities of the profession. Depending on the subareas and the nature of study, all papers mentioned at least one of the following criteria: expansion of target-audience, renewal of practices, political direction, defined theoretical approach or adequate technical competence, sometimes relating each other. In short, psychologist s social commitment is a contradictory issue which have earned projection in scientific literature, reiterating the historical custom of evaluate the psychologist profession. As conclusion, it is regarded as indispensable to intensify the reflection about the role whose psychologist plays in a class-cleaved society and the limits and potentials of his performing in that framework.